2011
DOI: 10.1007/s10658-011-9755-9
|View full text |Cite
|
Sign up to set email alerts
|

Chalara fraxinea is an invasive pathogen in France

Abstract: Decline induced by Chalara fraxinea is an emerging disease that severely affects ash stands in Europe. The disease appears to have an invasive spread from East to West of Europe in the last decade. The teleomorphic stage, Hymenoscyphus pseudoalbidus, that occurs as apothecia on ash rachis in the litter was recently described. The origin of ash decline remains unclear as a cryptic species, H. albidus, a long-established fungus in Europe, could be present in the same niche, and as in Switzerland, H. pseudoalbidu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
113
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(123 citation statements)
references
References 27 publications
(44 reference statements)
8
113
0
2
Order By: Relevance
“…Its role as the main pathogenic agent of the current ash dieback epidemic in Europe has been confirmed in this and several other studies and is beyond dispute (Kowalski 2006;Kowalski and Holdenrieder 2009b;Bakys et al 2009b;Husson et al 2011;Gross et al 2014). The necrotic lesions formed in the initial stage of disease on twigs and young side branches were typical, and similar to those described for H. fraxineus after natural infections (Kowalski and Holdenrieder 2008) and artificial inoculations (Kowalski and Holdenrieder 2009b;Bakys et al 2009a, b).…”
Section: Occurrence Of Hymenoscyphus Fraxineussupporting
confidence: 74%
See 2 more Smart Citations
“…Its role as the main pathogenic agent of the current ash dieback epidemic in Europe has been confirmed in this and several other studies and is beyond dispute (Kowalski 2006;Kowalski and Holdenrieder 2009b;Bakys et al 2009b;Husson et al 2011;Gross et al 2014). The necrotic lesions formed in the initial stage of disease on twigs and young side branches were typical, and similar to those described for H. fraxineus after natural infections (Kowalski and Holdenrieder 2008) and artificial inoculations (Kowalski and Holdenrieder 2009b;Bakys et al 2009a, b).…”
Section: Occurrence Of Hymenoscyphus Fraxineussupporting
confidence: 74%
“…Husson et al (2011), who detected Hymenoscyphus species in 80 % of symptomatic F. excelsior samples using molecular methods and Hymenoscyphus-specific PCR primers, concluded that the remaining 20 % of lesions may have been the result of damage by abiotic factors or infection by other pathogenic fungi. Previously, before the invasion of H. fraxineus, similar lesions on branches and stems of ash trees could be caused by Hysterographium fraxini (Zogg 1944;Prihoda 1982;Cannon 1999).…”
Section: Occurrence Of Hymenoscyphus Fraxineusmentioning
confidence: 99%
See 1 more Smart Citation
“…A prominent example is sudden oak death (causal agent Phytophthora ramorum), which has caused extensive environmental damage to woodland communities in the western Uniited States since its introduction in 1995 (Rizzo and Garbelotto 2003) and currently poses a significant threat to heathland and woodland environments in the United Kingdom (Brasier et al 2004). Another example is ash dieback (Chalara fraxinea), a damaging fungal disease that has recently invaded a number of countries in Europe (Kowalski 2009, Chandelier et al 2011, Husson et al 2011, Timmermann et al 2011, Bari c et al 2012, Bengtsson et al 2013, prompting the rapid deployment of extensive surveying and control resources (Anonymous 2012a). Following the first discovery of an invading plant pathogen a regulatory agency must act quickly to mitigate the problem since management becomes disproportionately more costly and difficult with increasing pathogen incidence.…”
Section: Introductionmentioning
confidence: 99%
“…The full recognition of fungal and fungal-like diversity has long been hampered by a lack of diagnostic criteria, but the availability of improved molecular techniques now allows the recognition of fungal species consistent with the Evolutionary Species Concept (Taylor et al 2000). For example, detailed phylogenetical studies have demonstrated that the fungal lineage causing ash dieback was different from the indigenous European species Hymenoscyphus albidus, which is not pathogenic, and that it was conspecific to the Asian species formerly reported as Lambertella albida (Queloz et al 2011;Husson et al 2011;Zhao et al 2012). In many cases, species defined from morphological traits were shown to be pools of genetically isolated lineages that differed significantly in biologically relevant features such as geographic distribution and pathogenicity (Taylor et al 2000(Taylor et al , 2006.…”
mentioning
confidence: 99%